Model Hybrid Bureaucracy dalam Transformasi Digital Pelayanan Publik: Studi Komparatif Urban-Rural di Indonesia Pasca-Pandemi (2020–2025) - Bunga Ainia; Dhea Kartika Anatasya; Indri Ramadhani Putri; Jumiati Jumiati; Boni Saputra (Lembag, 2025)
Digital governance transformation through a hybrid bureaucracy model is considered the main adaptive solution in post-COVID-19 pandemic Indonesia. This study uses the systematic literature review (SLR) method based on PRISMA 2020 with a focus on Sinta and Scopus indexed articles for the 2020–2025 period, to examine the implementation of hybrid bureaucracy in urban and rural areas, and is supported by relevant classical theoretical literature as a basis for the conceptual framework. Results show that the 35% improvement in public service efficiency in urban areas, but only 12% in rural areas, is rooted in disparities in infrastructure and digital literacy. Three main challenges were identified: ASN resistance to technology, overlapping regulations, and budget constraints. Policy recommendations lead to accelerated harmonization of SPBE regulations, gamification-based training strategies, and special budget allocations for 3T (underdeveloped, frontier, and outermost) regions. This study provides an empirical basis for the development of an inclusive and equitable public service digital transformation strategy in Indonesia.